Shepard and Dark [videorecording (DVD)] - Shepard, Sam, 1943-2017; Dark, Johnny, 1940- ([Publisher not identified], 2013)
Sam Shepard and Johnny Dark met in the early '60s and remained close friends despite living very different lives. Shepard became a Pulitzer Prize winning playwright and an Academy Award-nominated author while Dark was a homebody with a penchant for photography and letter writing.